Global or regional jihad? Foreign fighters and al-Qaida rhetoric in al-Shabaab’s nationalistic rebellion - Andersen, Lars Erslev; Moe, Louise Wiuff (Politica, 2015)
Foreign fighters are seen as a great threat to Western countries. The “Syria warriors” have recently been in focus, but the debate started much earlier, with particular reference to the threat that is said to be posed by the Somali rebel group al-Shabaab. What is the empirical basis for the alleged link between regional conflicts, Jihad groups, and a growing threat to the West? Are there clear examples of al-Shabaab organizing attacks or recruiting fighters to return to the West to carry out terrorism? Empirical data from open sources and analysis of al-Shabaab indicate that this alleged link lacks empirical basis, but nevertheless is used to legitimize extending support to anti-terrorism initiatives and increasing the resources and powers of intelligence services.